Agro-environmental diagnosis on the crop family farm: Case study - Camelia Toma (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The utilization of a diagnosis method of the farm influence on the environment is quite opportune in the present context: (i) The environment is a strong component of agricultural policies and a diagnosis is needed to guide the implementation actions (agro-environmental measures, CAP subsidies, high value environmental certification, recognition of high natural value agricultural systems, conversion to organic farming, etc.); (ii) The impact of production techniques upon the environment becomes increasingly necessary to be evaluated along the quality product chains. The purpose of the method is to establish the current environment condition at a given moment, to put into evidence the ecological systems, to identify the risky practices and to suggest improvement modalities to farmers. At the same time, the diagnosis has the capacity to evaluate: (i) "the value added" of the environment, through a better nitrogen and organic fertilizers management; (ii) own natural resources (soil, weather, biodiversity, etc.); (iii) pressure upon water and energy, etc.; (iv) negative and positive effects upon the local eco-systems. The method has a double approach: a global one - analysis of the farm system and its practices (30 indicators, on a scale of 1 to 100 scores) and a thematic one - impact of the farming activity upon the different environment compartments (23 indicators, from 1 to 20 scores). The "DIALECT" method used for the agro-environmental diagnosis on a crop production farm yielded interesting results, specific to the Romanian agriculture, and certain indicators were comparable to the environmental indicators of similar groups of European agricultural holdings.
Keywords: 330; The DIALECT method; farm; agro-environmental diagnostic; questionnaires; indicators